Prawo rzymskie na wyspie Kos - lex Fonteia i zagadnienia przekładu prawniczego - Pieczonka, Joanna (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2012)
The author describes the legal act, called lex Fonteia, which was first enacted in Rome, then translated to Greek and introduced on the Cos island in the 1st century BC. Few issues are raised in the article concerning the legal language of this law and the Latin version of the text – especially there are discussed Latin equivalents of such verbs as μεταπορεύεσθαι and πράσσειν. Moreover, the article gives examples of potential syntactical and lexical Latinisms, which occur in the Greek edition of the law, and presents the problem of translating the legal phrasemes.
Keywords: Roman law; Greek law; lex Fonteia; translation; Kos